2013
DOI: 10.1002/chem.201301112
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Effects on Single‐Site Iron Catalysts for Water Oxidation

Abstract: Getting in tune: Systematic tuning of the electronic properties of modular non-heme iron coordination complexes can be used to extract important information on the reaction mechanism and intermediates, which, in turn, help to explain the activity of these systems as water oxidation catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
117
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 42 publications
(17 reference statements)
6
117
0
Order By: Relevance
“…These experiments provided support for a mechanism in which a [ 396 To shed light on the mechanism of the final part of the reaction, that is, the generation of O 2 from the [Fe IV (O)-(OH 2 )(L N4 )] 2+ species, the authors decided to address this in a subsequent study. 397 In this study, a family of structural analogues of complex 303 ( Figure 81) hosuing different This work gave additional insight into the mechanism of the crucial O−O bond formation and also revealed that structural modifications of the ligand backbone had a significant effect on the catalytic performance. Carrying out the reaction with 12.5 μM of complex 312 and 10.000 equiv of CAN at pH 0.7 resulted in the most efficient reaction, affording a TON of 180 over 2 h and a maximum TOF of 0.23 s −1 .…”
Section: Molecular Water Oxidation Catalysts Based On Ironmentioning
confidence: 96%
“…These experiments provided support for a mechanism in which a [ 396 To shed light on the mechanism of the final part of the reaction, that is, the generation of O 2 from the [Fe IV (O)-(OH 2 )(L N4 )] 2+ species, the authors decided to address this in a subsequent study. 397 In this study, a family of structural analogues of complex 303 ( Figure 81) hosuing different This work gave additional insight into the mechanism of the crucial O−O bond formation and also revealed that structural modifications of the ligand backbone had a significant effect on the catalytic performance. Carrying out the reaction with 12.5 μM of complex 312 and 10.000 equiv of CAN at pH 0.7 resulted in the most efficient reaction, affording a TON of 180 over 2 h and a maximum TOF of 0.23 s −1 .…”
Section: Molecular Water Oxidation Catalysts Based On Ironmentioning
confidence: 96%
“…1,2 While in attempts to mimic nature the first catalysts were based on manganese, more recently catalytically active compounds for water oxidation have been reported based on cobalt, 3-7 nickel, [8][9][10] iron, [11][12][13] copper, 14-20 ruthenium [21][22][23][24][25][26][27][28][29][30][31][32][33][34] and iridium. [35][36][37][38][39] Generally, the catalytic activity of these compounds is investigated using the oxidant (NH4)2[Ce(NO3)6] (CAN).…”
Section: Introductionmentioning
confidence: 99%
“…10,15,porphyrin, with a highly electron-deficient meso-dimethylimidazolium porphyrin, was the most effective catalyst. The O 2 formation rate was 170 nmol·cm −2 ·min −1 (k obs = 1.4 × 10 3 s −1 ) with a Faradaic efficiency near 90%.…”
mentioning
confidence: 99%